Augmentation of virulence related traits of pqs mutants by Pseudomonas quinolone signal through membrane vesicles. (3rd October 2014) - Bala, Anju; Kumar, Lokender; Chhibber, Sanjay; Harjai, Kusum
<x xml:space="preserve">Abstract</x> Pathogenicity of opportunistic Pseudomonas aeruginosa is mediated through expression of different virulence determinants, most of which are under the control of quorum sensing. Besides acylhomoserine lactones, P. aeruginosa produces Pseudomonas quinolone signal (PQS) molecules which co‐regulate expression of overlapping subset of genes. In the present study, effect of mutations in the pqs genes on the production of virulence factors, biofilm, and membrane vesicles (MVs) was studied using standard strain and isogenic pqs mutants of P. aeruginosa. Mutations in pqs genes severely reduced elastase, pyocyanin, siderophores, biofilm formation, and production of MVs. Further, effect of synthetic PQS on virulence of P. aeruginosa and its correlation with MVs was investigated. Supplementation of PQS resulted in enhancement of phenotypic expression of virulence factors and biofilm forming capacity of these strains. Restoration of virulent phenotype of mutants in presence of PQS indicated that PQS system play an important role in the virulence of P. aeruginosa. In addition, PQS also induced substantial release of MVs in all strains. When vesicles containing natural PQS were added to the mutants, significant increase in production of virulence factors was observed. This augmentation of the virulence traits may be associated with the efficient delivery of PQS among bacterial cells, which could be one possible mechanism of pqs system contributing to the overall virulence of P. aeruginosa.